Saving Behavior Factors that Influence Generation Z Saving Behavior - Qurotul Aini, Qurotul Aini; Dianta, Karuniana; Pratama, Aditya (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This study’s goal is to ascertain the factors that influence generation Z’s saving behavior. The problem studied is that many young people today are still not aware of saving. In various studies there are theories of saving behavior, financial inclusion, and financial literacy, so a systematic literature review is needed to reaffirm the definition, concept, measurement and operationally in related dimensions and indicators. The author uses grounded theory with a literature study method in this qualitative research so as to provide the right position in the direction of updating indicators such as saving behavior, financial inclusion, and financial knowledge. The literature study’s findings indicate that financial literacy influences saving behavior and financial inclusion, financial inclusion affects saving behavior. Recommendations to future researchers to be able to follow up this research in analyzing other factors, on a wider scale, and measuring qualitatively and empirically.